Issues in Federal Debt Management (USA : Federal Reserve Bank of Boston, 1973)
All papers and comments of discussants included in this volume were presented at the conference sponsored by the Federal Reserve Bank of Boston in June 1973.
Proceedings of a conference held in June 1973
osc 20/06/17
Loans
Keywords: Debt Management